Physical activity profile of 2014 FIFA World Cup players, with regard to different ranges of air temperature and relative humidity - Chmura, P.; Konefal, M.; Andrzejewski, M.; Kosowski, J.; Rokita, A.; Chmura, J. (International Journal of Biometeorology, 2017)
The study attempts to assess changes in soccer players` physical activity profiles under the simultaneous influence of the different combinations of ambient temperature and relative humidity characterising matches of the 2014 FIFA World Cup hosted by Brazil. The study material consisted of observations of 340 players representing 32 national teams taking part in the tournament. The measured indices included total distances covered; distances covered with low, moderate, or high intensity; numbers of sprints performed, and peak running speeds achieved. The analysis was carried out using FIFA official match data from the Castrol Performance Index system. Ultimately, consideration was given to a combination of three air temperature ranges, i.e. below 22 °C, 22-28 °C, and above 28 °C; and two relative humidity ranges below 60 % and above 60 %. The greatest average distance recorded (10.54 ± 0.91 km) covered by players at an air temperature below 22 °C and a relative humidity below 60 %, while the shortest (9.83 ± 1.08 km) characterised the same air temperature range, but conditions of relative humidity above 60 % (p = 0.001). Two-way ANOVA revealed significant differences (p = 0.001) in numbers of sprints performed by players, depending on whether the air temperature range was below 22 °C (40.48 ± 11.17) or above 28 °C (30.72 ± 9.40), but only where the relative humidity was at the same time below 60 %. Results presented indicate that the conditions most comfortable for physical activity on the part of players occur at 22 °C, and with relative humidity under 60 %.